0
$\begingroup$

A worker wishing to retire for $20$ years would be paid an advance pension of $A=6000$ euro. The capital required for this is to be paid in the course of $15 $ years by successively paid annual contributions. At the beginning of the accumulation period, the deposit is once $K_0=10,000 $ Euro. How much are the annual contributions to be paid if the interest rate is $ q=4 \% $ during the entire term?

$$$$

I have done the following:

Let $X$ be the amount of the annual contributions.

After 15 years the present amount will be $$K_{15}=K_0 \cdot (1+q)^{15}+X\sum_{i=0}^{14}(1+q)^i=K_0 \cdot (1+q)^{15}+X\frac{(1+q)^{14+1}-1}{1+q-1} \\ =K_0\cdot (1+q)^{15}+X\frac{(1+q)^{15}-1}{q}$$ right?

After that, after the 20 years the present value will be $$K_{15} \cdot (1+q)^{20}-A\sum_{i=0}^{19}(1+q)^i=K_{15} \cdot (1+q)^{20}-A\frac{(1+q)^{19+1}-1}{1+q-1} \\ =K_{15} \cdot (1+q)^{20}-A\frac{(1+q)^{20}-1}{q}$$ right?

After the 20 years the value must be $0$, or not?

So, we have the following: $$K_{15} \cdot (1+q)^{20}-A\frac{(1+q)^{20}-1}{q}=0 \\ \Rightarrow \left ( K_0 \cdot (1+q)^{15}+X\frac{(1+q)^{15}-1}{q}\right )\cdot (1+q)^{20}-A\frac{(1+q)^{20}-1}{q}=0 \\ \Rightarrow K_0 \cdot (1+q)^{35}+X\frac{(1+q)^{15}-1}{q}\cdot (1+q)^{20}=A\frac{(1+q)^{20}-1}{q} \\ \Rightarrow X\frac{(1+q)^{15}-1}{q}\cdot (1+q)^{20} = A\frac{(1+q)^{20}-1}{q}-K_0 \cdot (1+q)^{35} \\ \Rightarrow X = \frac{A((1+q)^{20}-1)}{ (1+q)^{20}((1+q)^{15}-1)}-\frac{K_0\cdot q \cdot (1+q)^{35}}{ (1+q)^{20}((1+q)^{15}-1)} \\ \Rightarrow X = \frac{A((1+q)^{20}-1)}{ (1+q)^{20}((1+q)^{15}-1)}-\frac{K_0\cdot q \cdot (1+q)^{15}}{(1+q)^{15}-1}$$ Is this correct so far? How could we continue?

$\endgroup$
  • 2
    $\begingroup$ I suggest (opposite to convention) to replace your $1.04$ 's and $000$'s by something like $a$ and $b$. It would look much easier to read. Half the audience wouldn't read the entire question in the way this is written. $\endgroup$ – Qwerty Nov 29 '16 at 16:21
  • 1
    $\begingroup$ The more , the merrier! $\endgroup$ – Qwerty Nov 29 '16 at 16:35
  • 1
    $\begingroup$ I went through your calculations. I think you are right. Since $A,K_0,q$ are known, you know $X$. So what to continue? $\endgroup$ – Qwerty Nov 29 '16 at 16:48
  • 1
    $\begingroup$ Should be. Why do you think it is not? $\endgroup$ – Qwerty Nov 29 '16 at 17:33
  • 1
    $\begingroup$ Looks like the latter thought! $\endgroup$ – Qwerty Nov 29 '16 at 17:56
1
$\begingroup$

We suppose all payments are made at the end of each period.

Let be $n=15$, $m=20$, $K_0=10\,000$, $A=6\,000$, $q=4\%$ and $X$ the requested payment.

One way to solve the problem is to use the present values. The present value must satisfy $$ K_0+Xa_{\overline{n}|q}= A\; _{n|}a_{\overline{m}|q} $$ where $$a_{{\overline {n}}|q}={\frac {1-v^{n}}{q}},\quad v=\frac{1}{1+q},\qquad _{n|}a_{\overline{m}|q}=v^n a_{\overline{m}|q}=a_{\overline{n+m}|q}-a_{\overline{n}|q}$$ and then $$ X=\frac{A\; _{n|}a_{\overline{m}|q}-K_0}{a_{\overline{n}|q}} $$ Another way is to impose that the future value of the payments of the first periods at time $n$ is equal to the present value of the pension at time $n$, that is $$ K_0(1+q)^n+Xs_{\overline{n}|q}= A\, a_{\overline{m}|q} $$ where $$s_{{\overline {n}}|q}={\frac {(1+q)^{n}-1}{q}}$$ and then $$ X=\frac{A\;a_{\overline{m}|q}-K_0(1+q)^n}{s_{\overline{n}|q}} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.